Occupational choice and the spirit of capitalism - Matthias Doepke; Fabrizio Zilibotti (Institute for the Study of Labor (IZA), 2007)
The British Industrial Revolution triggered a reversal in the social order whereby the landed elite was replaced by industrial capitalists rising from the middle classes as the economically dominant group. Many observers have linked this transformation to the contrast in values between a hard-working and thrifty middle class and an upper class imbued with disdain for work. We propose an economic theory of preference formation in which both the divergence of attitudes across social classes and the ensuing reversal of economic fortunes are equilibrium outcomes. In our theory, parents shape their children's preferences in response to economic incentives. If financial markets are imperfect, this results in the stratification of society along occupational lines. Middle-class families in occupations that require effort, skill, and experience develop patience and work ethic, whereas upper-class families relying on rental income cultivate a refined taste for leisure. These class-specific attitudes, which are rooted in the nature of pre-industrial professions, become key determinants of success once industrialization transforms the economic landscape.
Keywords: 330; Soziale Schicht; Sozialer Wandel; Finanzmarkt; Unvollkommener Markt; Leistungsmotivation; Sozialgeschichte; Industrialisierung; Großbritannien